2021
DOI: 10.1177/08969205211055863
|View full text |Cite
|
Sign up to set email alerts
|

The Perfect Storm: A Subcultural Analysis of the QAnon Movement

Abstract: In this study, we examine the social phenomenon known as ‘QAnon’. While QAnon is typically thought of as an exclusively online cultural phenomenon, and thus easily dismissed, it has played a significant role in promoting physical acts of violence—including multiple murders and the attack on the United States Capital on 6 January 2021. Utilizing a qualitative analysis of 300 hours of QAnon-related content, we argue that the widespread beliefs held by QAnon supporters were only possible due to the confluence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…These activities spur operations to confront and expose the QAnon conspirators on social media (e.g. @QAnonAnonymous [22]), amongst which some of our hacktivists have a direct role in "dismantling the Qanon infrastructure" [P2].…”
Section: Leaking Doxing and Deplatformingmentioning
confidence: 99%
“…These activities spur operations to confront and expose the QAnon conspirators on social media (e.g. @QAnonAnonymous [22]), amongst which some of our hacktivists have a direct role in "dismantling the Qanon infrastructure" [P2].…”
Section: Leaking Doxing and Deplatformingmentioning
confidence: 99%
“…Conner and MacMurray conducted a content analysis of 300 hours of QAnon video and audio, participated in the GreatAwakening messageboard and QAnon-related Telegram channels, and attended livestreamed events conducted by Conner and MacMurray (2021). They found that influencers played a vital role in spreading the conspiracy theory and the associated movement.…”
Section: Situating Qanon Among Conspiracy Theoriesmentioning
confidence: 99%
“…Almost half (48%) of the QAnon supporters earned $50,000 or less. Conner and MacMurray (2021) argue that the QAnon is most popular with those who have been hardest hit by the changes in labor structures that were outcomes of neoliberal restructuring. Their secondary analysis of the IPSOS/NPR poll found that when the geographic region was controlled for, QAnon believers largely came from suburban and rural communities (Conner and MacMurray 2021).…”
Section: Precarity From Belowmentioning
confidence: 99%
See 2 more Smart Citations